Intrinsic instructional goal adoption increases autonomy-supportive teaching: A randomized control trial and intervention. (June 2021) - Jang, Hye-Ryen; Reeve, Johnmarshall
Abstract: Goal contents theory (GCT) stresses the benefits of intrinsic goal pursuit. To extend this research to teachers, the present investigation conducted two experiments to apply GCT's principles to the classroom to test for the causal, facilitating effect of teachers' intrinsic instructional goals on the new benefit of autonomy-supportive teaching. Study 1 was a laboratory study with 156 college students randomly assigned into one of three conditions: intrinsic instructional goal-personal growth, intrinsic instructional goal-relationship growth, or no-goal. Planned comparisons showed that teachers who pursued an intrinsic instructional goal showed more autonomy-supportive teaching than did teachers in the no-goal condition. Study 2 was a classroom-based intervention with 26 experienced K-12 teachers and their 538 students. Teachers were randomly assigned into either an intrinsic instructional goal intervention or a no-intervention control condition. Repeated-measures ANCOVAs showed that intrinsic instructional goals were malleable and led to significantly greater autonomy-supportive teaching, according to trained raters and teachers but not their students. Teachers in the intervention condition also reported greater need satisfaction and teaching efficacy. These findings confirm the teacher benefits of adopting intrinsic instructional goals and therefore open up a new and promising area for future research. Highlights: Teachers' intrinsic instructional goals (IIG) can be manipulated. The current study presented the first-ever IIG intervention for teachers. Manipulated IIG increased autonomy-supportive style. Manipulated IIG increased teachers' needs satisfaction and teaching efficacy.